Moms are survivors, because our kids are more ours': narratives of middle-class, white mothers in Cape Town - Worthington, Deborah (Social Anthropology, 2015)
This paper focuses on how white, middle class South African mothers, living within a 60-kilometre radius of Cape Town's Central Business District, juggle their childcare and work responsibilities. Through use of multi-sited ethnography, I was able to enter the lives of ten white, middle-class South African mothers aged between early forties to early fifties. The data collected was obtained through participant observation, casual conversations and formal, semi-structured, one-on-one interviews. This minor thesis draws on a body of literature that focuses on the multiple paradoxes mothers' face, such as, the traditional gendered notions of what it means to be a "good" mother, the challenges of time, and coping strategies. This paper explores how the research participants reconstituted their lives after having children. Through an analysis of conversations and field observations this minor thesis demonstrates the everyday circumstances of living through and negotiating daily life as a middle class, white mother in Cape Town, South Africa. In this minor thesis, I aim to demonstrate how parenthood is filled with fears and numerous challenges. The findings make strong case for researching the lives of such women who often suffer in silence.